Constrained Modal Analysis and Structure Improvement of Drive Gearbox of High-speed EMU - Wei Hao; Honghai Xu (Jixie chuandong)
Taking the drive gearbox of a high-speed EMU as the research object，uses APDL language to establish the constrained modal analysis parametric model of the gearbox，uses the spring element to simulate the joint surface between the shaft and the box，and the first four mode shape and the natural frequency of gearboxes are obtained through finite element analysis. By using the Sobol local sensitivity analysis method，the key structural parameters that affect the natural frequency of the gearbox is determined，the influence of key structural parameters on the natural frequency is analyzed. On this basis，the size parameters of the key structure improvements are carried out to increase the first and second order natural frequencies of the gearbox by more than 5%，the anti-vibration capability of the gearbox is improved. A theoretical basis for the improved design of the drive gearbox for high-speed EMU is provided.